ELDER ABUSE IN FORENSIC PRACTICE - Kristina Hadzhieva (Science & Research)

(untitled)
Elder abuse is a single or repeated act or lack of appropriate care that results in harm and suffering to a person. These acts constitute a violation of human rights and can be divided into several types: physical, sexual, mental and/or emotional abuse, financial and/or material abuse, abandonment and neglect (WHO, 2021). Physical abuse is the most common and recognizable type of elder abuse. The most common signs and symptoms of physical abuse are various traumatic injuries (bruises, abrasions, lacerations, cuts and stabbing injuries, etc.), which can be of varying duration (National Center of Elder Abuse). The purpose of the present study is to analyze, with the help of statistical maps, the social and household factors and the morphological characteristics of the disabilities, established in patients over the age of 65 who passed through the outpatient department of the Department of Forensic Medicine at the St. George UMHAT - Plovdiv. The retrospective study included 182 patients over the age of 65 who went through the outpatient office of the Department of Forensic Medicine in the city of Plovdiv over a 2-year period (2016-2017). The results of the statistical analysis largely correlate with those in foreign studies on the subject.